PENGARUH RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER), DAN INFLASI TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Ni Kadek Santi Suarniti; I Wayan Sukadana; I Wayan Widnyana (VALUES, 2021)
Stock Return is the value obtained as a result of investing activities, because a high enough stock return will be more attractive for investors to buy shares in the capital market. This study aims to test and obtain empirical evidence regarding the effect of Return On Asset (ROA), Debt To Equity Ratio (DER), and Inflation on stock returns in property and real estate companies listed on the Indonesia Stock Exchange. The population of this research is property and real estate companies listed on the Indonesia Stock Exchange in 2014-2018. The research sample was 41 companies which were determined based on purposive sampling method. The analytical tool used to test the hypothesis is multiple linear regression analysis. The results showed that Return on Assets (ROA) had a positive effect on stock returns, while the Debt To Equity Ratio (DER) and inflation had no effect on stock returns. In addition, Return on Assets (ROA), Debt to Equity Ratio (DER), and inflation simultaneously have a significant effect on stock returns. Further research can develop research using other variables such as interest rates and foreign exchange rates, as well as adding to the observation year period and using companies listed on the IDX so that the research results can be more comprehensive.